Mesocapnia aptera (Plecoptera: Capniidae) a new wingless winter stonefly from northern California, U.S.A. - Lee, Jonathan J. (Illiesia, 2011)
Mesocapnia aptera sp. n. is described from specimens collected in Mendocino County, California. The male and female are described, illustrated using scanning electron microscope micrographs, and compared to several Mesocapnia species and other apterous western capniids.
Keywords: entomologija; entomology; Plecoptera; vrbnice; stonefly; nove vrste; California; Capniidae; Kalifornija; Mesocapnia; new species; apterous; northern California